Copyright : rebalancing the public and private interests in the areas of education and research - Wang, Jia (Stellenbosch University, 2013)
The general public should have wide access to copyrighted materials for education and research. However, since the current copyright law system subtly favors copyright holders, it is time to re-evaluate copyright law to ensure it meets its original purpose of promoting the learning of the society. The research primarily focuses on how to broaden copyright limitations and exceptions for the public to access and use learning materials. Within the framework of the copyright law system, other mechanisms that allow users to access copyrighted materials at a reasonable price also are considered. Such mechanisms include an efficient collective copyright management system and various licensing schemes. In an information network environment, it is time for developing countries to reform copyright law in order to promote education and research. It is hoped the findings of this study not only benefit South Africa and People's Republic of China, but also provide insights and guidelines to other developing countries with similar conditions.
URI: http://hdl.handle.net/10019.1/85834
Keywords: China; Copyright; Economic aspects; Education and copyright law; Effect of copyright on ICT; Freedom of information and opinion; Globalization and education; Information and communication technology; Intellectual property; South Africa